The Influence of Spiritual Intelligence, Spiritual Congruence and Accounting Literacy on Attitude of Purchasing Halal Product Towards Intention to Purchase Among Generation Alpha - Azreen Jihan Mohd Hashim; Nurul Nazlia Jamil; Muhammad Majid; N Alia Fahada W Ab Rahman; Muhamad Azrin Nazri (Universiti Sultan Zainal Abidin, 2024)
Indexed by WOS/MyCite